The Transformation of the Toyota Kijang (1977–1996): From Commercial Vehicle to Symbol of Indonesian Family Culture through Advertising Strategy and Government Policy - Wulandari, Afrianti (Doctoral Program of Social Science Pasundan University, 2025)
This article examines the transformation of the Toyota Kijang from a simple commercial vehicle to an iconic family vehicle in Indonesia during the period 1977–1996. As part of the national policy through the Multipurpose Commercial Vehicle Program (KNBS), the Toyota Kijang was initially designed to meet the transportation and distribution needs of goods amidst national development. However, over time, this vehicle underwent a shift in function to become a family vehicle reflecting the economic stability and social aspirations of the Indonesian people. This research uses a historical method with a descriptive qualitative approach, which is based on the analysis of primary data from Television Republik Indonesia (TVRI) advertisement documentation, print media, and digital archives. The main focus of this study is Toyota's marketing communication strategy, particularly the use of mass media and emotional approaches in advertising, including the involvement of celebrities as endorsers. The analysis also includes the application of the marketing mix (7Ps): product, price, promotion, place, process, people, and physical evidence. The results of the study indicate that the success of the Toyota Kijang lies not only in the technical quality of the product, but also in the ability to adapt to changes in media policy, consumer cultural sensitivity, and the power of advertising narratives in building brand image. Through an integrated and contextual communication strategy, Toyota Kijang was able to occupy a central position in the Indonesian automotive landscape while simultaneously forming a new culture in the lives of middle-class families during the New Order era.